[en] AN ANALYSIS OF PRACTICES IN APPLYING SCRUM ON LARGE PROJECTS - EVANDRO OLIVEIRA DAS FLORES (MAXWELL, 2012)
[pt] Na literatura disponível hoje, encontram-se exemplos da utilização do Scrum em projetos e times pequenos, deixando um questionamento sobre a possibilidade de utilização desta metodologia em projetos e/ou times grandes. Esta dissertação tem por objetivo examinar casos práticos de empresas conhecidas onde foi utilizado Scrum em projetos grandes, enfatizando as dificuldades encontradas ao longo de todo processo e as soluções adotadas, destacando as práticas que levaram os projetos a obter sucesso. === [en] In today s writings, there are many examples of using Scrum in small teams and projects, leaving a knowledge gap about the possibility of applying Scrum in big teams and large projects. This work aims at presenting case studies in known companies where Scrum has been applied in large projects, emphasizing the roadblocks found throughout the process, and the solutions adopted, highlighting the practices that lead the projects to success.